LONDON TOURISM MARKET - SHENGNAN, Yin; Nedelea, Alexandru Mircea (Ecoforum Journal, 2018)
London is the most famous European destination bases on its culture, events, museum and heritage. This paper aims to use the ‘10As’ model, especially in Activities, Appreciation and Action to show London’s diverse events, the customer’s feeling of welcome and its well-planned future strategy. It adopts stakeholder analysis to identify the responsibilities of key stakeholders: leisure and business tourists and applies 4Ps marketing mix to present culture tourism as the main products.